As leituras pedagógicas de Sílvio Romero - Souza, Cristiane Vitório de (2006)
This work has as general objective to analyze the pedagogic readings undertaken by Sílvio Romero. The specific objectives are: to analyze the competences and practices of reading of the intellectual, to trace a profile of Sílvio Romero's Pedagogic Library and to understand as he appropriated of Herbert Spencer, Edmond Demolins, Paul Rousiers, Henri de Tourville and Vacher de Lapouge's readings. It uses as sources: its Library, especially, the Pedagogic Library, the works that wrote, the letters sent to the friends, the epoch literature and the literature about the epoch. Inspired by the New Cultural History it uses the indiciary method of Carlo Ginzburg, the document/ monument notion of Jacques Le Goff, the appropriation, reading competences, reading practices, oral reading, silent reading, materiality and representation notions of Roger Chartier, intellectual field, social capital and cultural capital concepts of Pierre Bourdieu. It concludes that the competences that he acquired as in the formal education as in the informal he became a critical reader of the national and foreign letters and he appropriated of that books in an active way, appropriating of the representations that allowed to think it the Brazilian education and rejecting the others.